Cmentarzysko ciałopalne ludności kultury łużyckiej w Starej, stan. 2, gm. Aleksandrów, woj. piotrkowskie - Szukała, Mirosław (Acta Universitatis Lodziensis. Folia Archaeologica, 1991)
In 1977 and 1978 excavations in burial ground in Stara were led by Regional Museum in Piotrków Trybunalski (M. Gąsior and M. Szukała). The surface of 450 m2 was outcroped revealing 30 graves. Moreover, 2 graves were accidentaly discovered. It can be assumed that about half of the burial ground was examined. Materials coming from excavations are on display of Piotrków Museum. In all, 32 graves were discovered in the burial ground and all of them were of cinevary urn shape. 10 graves were preserved in fairly good condition 14 were damaged and 8 graves were destroyed. No shape of grave hollows were observed. The mean depth of graves was 30-50 cm (from the present surface of the ground to the upper parts of cinevary urns). All graves with the exeption of the object no 21 consisted of 1 urn, the object no 21 consisted of 2 small vessel of one of which could function as a countershaft; because of damages in upper parts of vessels it is impossiblle to state it clearly. In 9 graves among burnt bones some gifts of the grave were found-small objects made of bronze, in 7 graves-small not very characteristic fragments of clay vessels. The weight of burnt bones was from 0,01 to 1,95 kg in 2 graves some charcoals scattered among bones were found. Graves are typical for Lusatian culture in that period and they are not different from others known in Mid-Poland. Pottery is the most numerous group of findings. 35 specimens of vessels preserved in different conditions and 7 sets of small fragments were found. Majority of vessels was reconstructed, some of them were preserved as a whole. According to the division of R. Mikłaszewska and J. Miśkiewicz vessels can be divided into the following types: - double-cone vessels (4 specimens), tureens (20 specimens), - vessels between double-cone ones and tureens ( 2 specimens), - amphoras (3 specimens), a bucket (1 specimen) and others (1 pice), - unidentified (4 specimens). Generally speaking, forms of vessels are more like the pottery from regions between the Warta and the Pilica rivers than the pottery coming from the region of the Vistula and the Pilica rivers. An ornament in from of different types of diagonal notches on the biggest swelling of the pad was found on eight vessels. The tureen of five handles from the object no 6 was treated as the most interesting vessel. Moreover, 9 bronze objekts – different kinds of spirals and rings and the object the use of which in know clearly known (ferrule?) were found. As regards the culture the burial ground was classified into secondary zone of Mid-Polish Lusatian culture with clear influences of the group from the Upper Silesia – Little Poland. The chronology of burial ground dates back to the end of the IV period of the Bronze Age and the end of the V period.